MANAGEMENT ASPECT OF THE PROBLEM OF NARCOTIC DRUGS USE - S. Yu. Soboleva (Фармакоэкономика, 2016)
The use of narcotic drugs in healthcare system nowadays is characterized by lawful aspects prevalence over medical, bioethics, economic and social aspects. The paper highlights the management imbalance in the system of record and control of narcotic drugs and suggests using in its decision real management tools: functional and process approaches as well as balance score card. The operation definition will allow to identify the ineffective phases, functional overlaps and basic losses in the process of narcotic drugs turnover while balance score card implementation will help to reveal the anticipatory indexes of efficient use of such medication.